2007
DOI: 10.1128/aem.01498-06
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Mineralization of Nanomolar Concentrations of the Herbicide Dichlobenil and Its Persistent Metabolite 2,6-Dichlorobenzamide by Aminobacter spp. Isolated from Dichlobenil-Treated Soils

Abstract: Aminobacter type strains not previously exposed to dichlobenil or BAM were capable of degrading nonchlorinated structural analogs. Combined, these results suggest that closely related Aminobacter strains may have a selective advantage in BAM-contaminated environments, since they are able to use this metabolite or structurally related compounds as a carbon and nitrogen source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 39 publications
(58 reference statements)
7
97
0
Order By: Relevance
“…The same pattern was recently observed in a study focusing on nanomolar degradation and mineralization of the pesticide residue 2,6-dichlorobenzamide (BAM) by Aminobacter sp. strains (41). This study confirmed that there was extensive degradation of BAM despite the low extent of mineralization measured using 14 CO 2 from [ring-14 C]BAM.…”
Section: Discussionsupporting
confidence: 73%
“…The same pattern was recently observed in a study focusing on nanomolar degradation and mineralization of the pesticide residue 2,6-dichlorobenzamide (BAM) by Aminobacter sp. strains (41). This study confirmed that there was extensive degradation of BAM despite the low extent of mineralization measured using 14 CO 2 from [ring-14 C]BAM.…”
Section: Discussionsupporting
confidence: 73%
“…However, Aminobacter, which is phylogenetically close to the Mesorhizobium species, can utilize an amine compound as carbon source. 38,39) Based on these reports, it is suggested that M. loti MAFF303099 also utilizes various amine compounds as carbon sources or nitrogen sources. Because mll1632 has narrow substrate specificity for -amino acid, it is not expected to prove responsible for amine utilization.…”
Section: Experimental Investigation Of the Functions Of The Putative mentioning
confidence: 99%
“…MSH1 [9] used in this study, MSH1-GFP, was fluorescently tagged. The 13 SFIs used were isolated from SF material from two drinking water treatment plants [11]: Acidovorax sp.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Therefore, bioaugmentation of SFs has been proposed as an alternative strategy, by the addition of a specialized BAM mineralizer such as Aminobacter sp. MSH1 [9]. However, studies of this type of bioaugmentation of drinking water ecosystems rarely address how exactly the pesticide degrader interacts with the resident community, and other such fundamental ecological questions [10].…”
Section: Introductionmentioning
confidence: 99%